Analysis of Multicultural Education Values in the Islamic Religious Education and Ethics Textbooks for Grade-XI Senior High School - Bahjata, Syafa; Fihris, Fihris (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2025)
This study aims to analyze the multicultural education values contained in the Islamic Religious Education and Ethics textbooks for grade XI of Senior High School/Vocational School. Using a Critical Discourse Analysis (CDA) approach, the research focuses on the representation of multicultural values in both textual and visual content. Data were collected through literature review and documentation, while the analysis involved three stages: description, interpretation, and explanation. The primary data source is the 2021 first edition of the Islamic Religious Education and Ethics textbook published by the Ministry of Education, Culture, Research, and Technology. The findings reveal that the textbook incorporates values such as tolerance, equality, justice, democracy, and humanism, which are represented through 289 textual narratives and 105 visual illustrations. CDA also shows that these values are reflected in subchapters covering Islamic insights, inspirational stories, character development, and reflections. The analysis of visuals further illustrates multicultural discourses related to equality, humanism, democracy, and tolerance in educational and social contexts. The study concludes that the textbook can serve as a vital tool in promoting multicultural awareness and building student character. It also offers valuable insights for textbook authors, educators, and policymakers to create more inclusive and culturally responsive educational materials in response to Indonesia's pluralistic society.